THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON COMPANY PERFORMANCE WITH PROFITABILITY AS AN INTERVENING VARIABLE - Dewi Kusuma Wardani; Yohana Gabrielis Mura Maing (Pusat P2M Politeknik Negeri Batam, 2024)
This research aims to analyze the influence of corporate social responsibility on company performance with profitability as an intervening variable in mining companies listed on the Indonesia Stock Exchange (BEI). This research uses a descriptive quantitative approach with the research sample consisting of 21 mining companies listed on the IDX during the 2017-2022 period. The analytical method used is multiple regression analysis and path analysis. The research results show that corporate social responsibility has a positive effect on company performance, profitability has a positive effect on company performance, corporate social responsibility has a positive effect on profitability and profitability is proven to mediate the effect of corporate social responsibility on company performance.